Linearity and stationarity of G7 government bond returns - Liew, Venus Khim-Sen; Qiao, Zhuo; Wong, Wing-Keung (Economics Bulletin, 2010)
This study investigates the linearity and stationarity properties of government bond returns for the G7 economies. Our results from Luukkonen et al. (198 8) linearity test reveal the nonlinear nature of all of the G7 bond returns. Furthermore, we had determined that they are stationary by the Kapetanios et al. (2003) nonlinear unit root test. In sum, it can be concluded that G7 government bond returns are stationary but possess a nonlinear feature. Our findings provide useful information for researchers interested in bond markets